Analisis Kinerja Aparatur Sipil Negara Pada Bagian Umum Sekdakab Serdang Bedagai - Delvi Windy Aulia Manik; Agung Suharyanto; Yurial Arief Lubis (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2023)
This article or writing aims to find out and describe the performance of the State Civil Apparatus in the General Section of the Regional Secretariat Of Serdang Bedagai Regency based on their duties. The problem is focused on the results of ASN work based on the intructions of the Regional Secretary when loading a coordination meeting that invites all apparatus to show an attitude of loyalty at work, then ability, innovation, and best performance as well as improving ASN discipline. Thus, those who do not comply will be given strict action. In order to approach this problem, Sedarmayanti’s theoretical reference is used which includes measurement such as work performance, expertise, behavior, and leadership. The data were collected based on data collection techniques through observation, interviews, and documentation and analyzed qualitatively. The data analysis technique used is data reduction, data presentation, and conclusion drawing. This study concludes that the performance of ASN in the general section of the Regional Secretariat of Serdang Bedagai Regency which has been analyzed from work performance, expertise, behavior, and leadership can be said to be good with proper and optimal execution and completion of work.